Conservation Genomics in a Changing Arctic. (February 2020) - Colella, Jocelyn P.; Talbot, Sandra L.; Brochmann, Christian; Taylor, Eric B.; Hoberg, Eric P.; Cook, Joseph A.
Abstract : Although logistically challenging to study, the Arctic is a bellwether for global change and is becoming a model for questions pertinent to the persistence of biodiversity. Disruption of Arctic ecosystems is accelerating, with impacts ranging from mixing of biotic communities to individual behavioral responses. Understanding these changes is crucial for conservation and sustainable economic development. Genomic approaches are providing transformative insights into biotic responses to environmental change, but have seen limited application in the Arctic due to a series of limitations. To meet the promise of genome analyses, we urge rigorous development of biorepositories from high latitudes to provide essential libraries to improve the conservation, monitoring, and management of Arctic ecosystems through genomic approaches. Highlights: As a bellwether for global change, the Arctic is a model for questions pertinent to the persistence and management of biodiversity. Genomic analyses are transforming our understanding of past Arctic communities, including organismal responses to historic climate oscillations that structured contemporary ecosystems. Accelerating environmental change in the Arctic requires fine-scale genomic approaches to recognize, document, manage, and monitor the pace of biotic disruption. Altered species ranges in the Arctic expand opportunities for hybridization, altered selection regimes, range shifts, and the spread of pathogens and disease; these and other biological attributes can now be revealed with unprecedented power using genomics. Geographically broad and temporally deep biorepositories of Arctic flora and fauna should be built through international collaborations that leverage existing infrastructure, including field stations, seed banks, and museums, as these specimens will be essential to understanding and recording changing conditions.